2014
DOI: 10.1073/pnas.1408988111
|View full text |Cite|
|
Sign up to set email alerts
|

Harm to others outweighs harm to self in moral decision making

Abstract: Significance Concern for the welfare of others is a key component of moral decision making and is disturbed in antisocial and criminal behavior. However, little is known about how people evaluate the costs of others’ suffering. Past studies have examined people’s judgments in hypothetical scenarios, but there is evidence that hypothetical judgments cannot accurately predict actual behavior. Here we addressed this issue by measuring how much money people will sacrifice to reduce the number of painful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
339
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(364 citation statements)
references
References 46 publications
22
339
1
2
Order By: Relevance
“…An important aim of our study was to explain what might drive variability in prosocial learning (1,(20)(21)(22). We identify evidence of a mechanism linking variability in empathy to variability in prosocial behavior, with highly empathic individuals having an increased learning rate, and stronger sgACC PE signals, for other people's rewards.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An important aim of our study was to explain what might drive variability in prosocial learning (1,(20)(21)(22). We identify evidence of a mechanism linking variability in empathy to variability in prosocial behavior, with highly empathic individuals having an increased learning rate, and stronger sgACC PE signals, for other people's rewards.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, although humans have a remarkable inclination to engage in prosocial behaviors, there are also substantial individual differences (1,(20)(21)(22). Empathy, the capacity to vicariously experience and understand the affect of others (23)(24)(25)(26)(27), has been hypothesized to be a critical motivator of prosocial behaviors (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…By contrast, when allocating physical harm to themselves and others, seminal work by Crockett et al has shown that people are hyperaltruistic (3,4). Specifically, people are willing to forego more reward to reduce others' pain than to spare themselves from harm, suggesting that they value others' welfare more than their own (3). The tension between selfish and (hyper)altruistic views of human decision making calls into question whether the principles guiding moral decisions are the same when distributing rewards versus harms.…”
mentioning
confidence: 99%
“…Economists typically characterize human decision makers as profoundly selfish when distributing rewards among themselves and others (1,2). By contrast, when allocating physical harm to themselves and others, seminal work by Crockett et al has shown that people are hyperaltruistic (3,4). Specifically, people are willing to forego more reward to reduce others' pain than to spare themselves from harm, suggesting that they value others' welfare more than their own (3).…”
mentioning
confidence: 99%
“…These findings may indicate that the worst possible outcome carries more weight when deciding for others than for self, perhaps because choosing for others has potential moral consequences whereas choosing for oneself does not. This idea finds additional support in a recent study where participants chose whether to inflict painful electric shocks on either themselves or an anonymous other person in exchange for money (11). Strikingly, most people were more averse to inflicting pain on others than themselves.…”
mentioning
confidence: 81%